Foreign Academics in China - Cai, Yuzhuo; Braun Střelcová, Andrea; Marini, Giulio; Huang, Futao; Xu, Xin (International Higher Education, 2022)
This article examines the experience of international academics in mainland China. The emerging trend of foreign academics moving into long-term, full-time positions in Chinese universities is an underreported phenomenon in research. This article discusses the following questions: Who are the foreign academics in China? What motivates them to go and work there? What are their expected roles in local academia? Are they satisfied with their jobs? Are they going to stay in China?